Water Balance Analysis in Plantations of Strawberries, in the Commune of San Pedro - Soto-Gomez, J; Carrasco-Armijo, R; Seguel-Gonzalez, F (Institute of Electrical and Electronics Engineers Inc., 2017)
This work analyzes the agro-climatic variables and the water requirements by evapotranspiration for strawberry plantations in the commune of San Pedro. Correlation analysis, principal components analysis, k-means of the time series of the agro-climatic variables and evapotranspiration are used. The periods with need of water are classified to implement a water balance controller. © 2017 IEEE.